Bidirectional GHz bandwidth amplified spontaneous emission generation and high output power single-pass optical amplification through a hot Cs vapor cell - Lee, Mingyu; Ryu, Siheon; Kim, Seokjin; Hong, Seongjin; Lee, Yong Soo; Yeom, Dong Il; Oh, Kyunghwan (Optics Continuum, 2022)
We report the characteristics of GHz bandwidth amplified spontaneous emission (ASE) from a hot Cs atom vapor cell, where the optical feedback was inhibited. When pumped by an 852 nm laser, both forward and backward ASE output near 894 nm showed a nonlinear increase in its power without a pump power threshold. A continual decrease in spectral width down to 4.7 GHz was experimentally observed as the ASE output power increased. Using the same vapor cell, we injected a 1mW signal to configure a single-pass optical amplifier, and we monitored the forward output both in temporal and spectral domains. We found the signal laser efficiently suppressed the ASE and obtained a large amplification factor over 700 at the pump power of 1.2 W.
Keywords: Amplified spontaneous emissions; Cs atoms; Emissions generations; Forward-and-backward; High output power; Optical amplifications; Power; Pump power; Single pass; Vapor cells